Advances in Psoriasis A Multisystemic Guide - Weinberg, Jeffrey M.; Weinberg, Jeffrey M.; Lebwohl, Mark.; Lebwohl, Mark. (Springer London : Imprint: Springer, 2014)
The understanding and management of psoriasis have evolved dramatically over the last decades and, as a result,  guidelines and treatment options have changed dramatically. To meet the need for a up-to-date practical resource in this area, the Editors have brought together a team of experts in the field to produce a highly informative and illustrated guide to the decision-making process for psoriasis. Advances in Psoriasis: A Multisystemic Guide provides physicians with a reference on the disease and its comorbidities and therapeutic options. It will help physicians further  their knowledge of the science and therapy of psoriasis. As well as practicing dermatologists, fellows in dermatology will find this book to be an essential training resource to learn about the treatment and management of psoriasis.